Autoimmune Encephalitis - Leypoldt, Frank (Eur Neurol Rev, 2013)
The term autoimmune encephalitis is used to describe a group of disorders characterised by symptoms of limbic and extra-limbic dysfunction occurring in association with antibodies against synaptic antigens and proteins localised on the neuronal cell surface. In recent years there has been a rapidly expanding knowledge of these syndromes resulting in a shift in clinical paradigms and new insights into pathogenic mechanisms. Since many patients respond well to immunosuppressive treatment, the recognition of these disorders is of utmost importance. In general, there are no brain-imaging modalities or biomarkers specific of these disorders other than the demonstration of the neuronal antibodies. A disease classification based on these antibodies provides information on prognosis and paraneoplastic aetiology. This article focuses on recent clinical advances, newly characterised antibodies and treatment approaches to these disorders.